2014
DOI: 10.1021/cg500661p
|View full text |Cite
|
Sign up to set email alerts
|

Seed-Assisted Synthesis of Crystalline Mo3VOx Oxides and Their Crystal Formation Mechanism

Abstract: The effects of the addition of crystalline Mo 3 VO x oxides (MoVO) seeds on an assembly of pentagonal [Mo 6 O 21 ] 6− building units with Mo and V octahedra for forming MoVO were investigated. In the absence of the seeds, the crystal phase of formed MoVO depended on the pH of the preparative solution, while the crystal phase of the formed MoVO was decided by the phase of the MoVO seeds used irrespective of the pH. Interestingly, MoVO were formed even in the pH condition where no crystals were formed in the abs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 31 publications
0
9
0
Order By: Relevance
“…The occurrence of trigonal (Mo,V)­O x inclusions in an orthorhombic grain may be attributed to similar synthesis conditions of both phases, which are most commonly obtained by a hydrothermal treatment at different pH values, , and/or may originate from the condensation of individual (Mo,V)­O x nanorods. In addition to the structural relaxation mechanism proposed above, which may originate from the differently connected {(Mo)­Mo 5 O 27 } units, minute local chemical and/or surface potential fluctuations may cause the formation of trigonal phases.…”
Section: Resultsmentioning
confidence: 99%
“…The occurrence of trigonal (Mo,V)­O x inclusions in an orthorhombic grain may be attributed to similar synthesis conditions of both phases, which are most commonly obtained by a hydrothermal treatment at different pH values, , and/or may originate from the condensation of individual (Mo,V)­O x nanorods. In addition to the structural relaxation mechanism proposed above, which may originate from the differently connected {(Mo)­Mo 5 O 27 } units, minute local chemical and/or surface potential fluctuations may cause the formation of trigonal phases.…”
Section: Resultsmentioning
confidence: 99%
“…We have reported that Tri-MoVO is formed from a precursor solution containing Keplerate-type polyoxometalate, {Mo 72 V 30 }, in which twelve {Mo 6 O 21 } 6– pentagonal units are linked with thirty VO 2+ groups. ,, During the hydrothermal process under the appropriate conditions, {Mo 72 V 30 } provides building blocks such as pentagonal {Mo 6 O 21 } 6– units, which are assembled with appropriate countercations to form Tri-MoVO. Müller et al reported that Keplerate-type {W 72 V 30 }, in which twelve {W 6 O 21 } 6– pentagonal units are connected with thirty VO 2+ , can be formed in a manner similar to {Mo 72 V 30 }. , In consideration of the location of W in the Tri-MoVO structure and the molecular similarity of {Mo 72 V 30 } and {W 72 V 30 }, we speculate that {W 72 V 30 } was formed by the introduction of the W source into the precursor solution as in {Mo 72 V 30 }.…”
Section: Resultsmentioning
confidence: 99%
“…Although the catalysts did not possess high quantities of total acid sites, medium and strong acid sites were present, notably in the samples calcined in oxygen (> 50%), which could be beneficial in the dehydration step. Several studies have shown that adequate strength of the acid sites is important because the adsorption of glycerol on relatively moderate strength acid sites favors the production of 3-hydroxypropa-nal, which consequently dehydrates to acrolein [41,42]. In the glycerol oxydehydration, the formation of CO and CO 2 is commonly associated with (Mo,V)O X species, the pure oxide phases, that promote complete oxidation of intermediates such as acetol, 3-hydroxypropane, and acrylic acid [16,45].…”
Section: Spent Catalystmentioning
confidence: 99%